2016
DOI: 10.1371/journal.pone.0167971
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TIMP-3 in Chondrocytes Produces Transient Reduction in Growth Plate Length but Permanently Reduces Adult Bone Quality and Quantity

Abstract: Bone development and length relies on the growth plate formation, which is dependent on degradative enzymes such as MMPs. Indeed, deletion of specific members of this enzyme family in mice results in important joint and bone abnormalities, suggesting a role in skeletal development. As such, the control of MMP activity is vital in the complex process of bone formation and growth. We generated a transgenic mouse line to overexpress TIMP3 in mouse chondrocytes using the Col2a1-chondrocyte promoter. This overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…In order to verify that [‐1A]TIMP‐3 exerts different effects compared with native, endogenous TIMP‐3, we extended the experiments to include native TIMP‐3. In contrast to transduction with [‐1A]TIMP‐3, native TIMP‐3 completely abrogated bone formation, consistent with our previous in vivo findings, in which overexpression of Col2a1‐driven TIMP‐3 resulted in significant reduction in bone mass . Similarly, expression of mRNA for alkaline phosphatase, osteocalcin, type I collagen, and RUNX‐2, reflecting osteogenic stimulation, was found to be elevated in [‐1A]TIMP‐3–transduced osteoblasts and suppressed by TIMP‐3 (Figure E).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In order to verify that [‐1A]TIMP‐3 exerts different effects compared with native, endogenous TIMP‐3, we extended the experiments to include native TIMP‐3. In contrast to transduction with [‐1A]TIMP‐3, native TIMP‐3 completely abrogated bone formation, consistent with our previous in vivo findings, in which overexpression of Col2a1‐driven TIMP‐3 resulted in significant reduction in bone mass . Similarly, expression of mRNA for alkaline phosphatase, osteocalcin, type I collagen, and RUNX‐2, reflecting osteogenic stimulation, was found to be elevated in [‐1A]TIMP‐3–transduced osteoblasts and suppressed by TIMP‐3 (Figure E).…”
Section: Resultssupporting
confidence: 90%
“…Evidence presented herein shows that STR/Ort mice expressing high levels of [‐1A]TIMP‐3, especially females, had significantly increased trabecular parameters and cortical bone thickness, compared with control mice and mice expressing low levels of [‐1A]TIMP‐3. We expected the opposite effect, since our previous studies demonstrated that high levels of WT TIMP‐3 overexpression in mouse cartilage led to lack of secondary ossification, and mice with intermediate levels of TIMP‐3 had reduced bone mass . It has already been shown that MMP deficiency (e.g., deficiencies of MMP‐9 and membrane type 1 MMP) can lead to developmental skeletal abnormalities .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, the MMP13 and ADAMTS5 are able to degrade COL II, lead to articular cartilage destruction and initiate osteoarthritis 53 - 56 . Meanwhile, TIMP3, a key anticatabolic factor and one of the endogenous inhibitors of MMP13 and ADAMTS5 57 - 59 , was also studied. The results showed that MoO 4 2- ions inhibited catabolic responses of co-cultured RCs indicative of downregulation of HIF-2α, MMP13, ADAMTS5 as well as upregulation of TIMP3.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculate that sustained TIMP-3 expression, and the consequent persistent inhibition of ADAM10, as well as the inhibition of other metalloproteinases, can have detrimental effects in vivo . In support of this hypothesis, transgenic mice overexpressing TIMP-3 in chondrocytes display abnormalities in bone development, including decreased osteoblast differentiation and reduction in growth plate length and bone mass 52 , 53 . Such a phenotype may be due to dysregulation of Notch signaling, which plays a crucial role in maintaining bone homeostasis by regulating proliferation and differentiation of both osteoblasts and osteoclasts 54 .…”
Section: Discussionmentioning
confidence: 86%